Resourcing issues: adherence to treatment: a major obstacle to reaching goal in type 2 diabetes - Gagliardino, Juan Jose (2004)
Diabetes is a chronic, progressive disease and achieving appropriate control of glycaemia and the other associated cardiovascular risk factors is essential to prevent its long-term complications. Currently, recovery and rehabilitation from the cardiovascular complications of diabetes are the major focus of diabetes care rather than primary and secondary prevention of diabetes and its complications. This focus, coupled with limited funding and other resource issues, means that diabetes care and outcomes are generally suboptimal. More efficient and effective management strategies, primarily based upon a broad educational approach including both those with diabetes and their care-givers will be essential in reducing the cost of diabetes and diabetes-related complications. Continuous education of patients and providers increases the quality of care and improves clinical and metabolic outcomes as well as reducing the cost of care and optimising human and financial resources. Thus, education will be a key strategy in minimising the growing burden of diabetes on society. Making these changes will require the co-operation of patients, their families, the community, healthcare policy makers, national governments and the pharmaceutical industry. Medical schools must also place more emphasis on educating doctors about chronic disease management using not only recovery and rehabilitation, but also prevention strategies, emphasising the importance of helping patients to participate in the control of their disease.